Editorial: Education in the age of artificial intelligence - Jarosław Charchuła; Mirosław Kowalski (Jesuit University Ignatianum in Krakow, 2024)
The progress of civilisation is the ground for enormous changes in the life of every human being. The development of information technology, telecommunications or multimedia is a huge step in the history of all civilisation. This evolution from the industrial era, where we were dealing with an industrial society, is moving us to an information society based on artificial intelligence (AI). Information is becoming the basis not only for the smooth functioning of all types of institutions - but also, and perhaps above all, for the educational process. The implementation of artificial intelligence in the education system is a topic that generates both enthusiasm and concern. On the one hand, the possibilities it offers in the context of education seem almost limitless, promising, among other things, the personalisation of teaching, the optimisation of teaching processes and support in the diagnosis and development of students' skills. On the other hand, there are questions about data security, ethics and the potential replacement of teachers by machines.